Family rituals in pediatric epilepsy : links to parental competence and adaptation. - Mendes, Teresa Paula Gameiro Pompeu (2022)
This cross-sectional study examined the associations between family ritual meaning and 3 indicators of parental adaptation (anxious and depressive symptoms and quality of life) via 2 dimensions of parental competence-satisfaction and efficacy-in parents of children with epilepsy. Two hundred Portuguese parents of children diagnosed with epilepsy for at least 6 months completed self-report measures assessing the main study variables. Our results showed that when parents reported stronger family ritual meaning, they also reported higher levels of parental satisfaction and efficacy, which were in turn were associated with lower psychological distress (anxious and depressive symptoms) and better quality of life of parents. This pattern of results was significant regardless of the severity of children's epilepsy, age group, and family socioeconomic level. In the context of pediatric epilepsy, empirical evidence was found for the role of family ritual meaning in being directly and indirectly associated with parents' adaptation outcomes by higher levels of parental satisfaction and efficacy. Focusing intervention targets on what families naturally do and recognize as their own ritual meaning may be a favorable route to address those at risk of psychological distress and lower quality of life.